2012
DOI: 10.1371/journal.pone.0037418
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary History of the Odd-Nosed Monkeys and the Phylogenetic Position of the Newly Described Myanmar Snub-Nosed Monkey Rhinopithecus strykeri

Abstract: Odd-nosed monkeys represent one of the two major groups of Asian colobines. Our knowledge about this primate group is still limited as it is highlighted by the recent discovery of a new species in Northern Myanmar. Although a common origin of the group is now widely accepted, the phylogenetic relationships among its genera and species, and the biogeographic processes leading to their current distribution are largely unknown. To address these issues, we have analyzed complete mitochondrial genomes and 12 nuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
57
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 48 publications
3
57
0
Order By: Relevance
“…Regardless of the reference genomes and treebuilding methods used, the genome phylogeny strongly supported the interspecific relationships shown in a previous tree based on the analyses of several nuclear genes ( Fig. 1) and significantly rejected the relationships represented in a tree based on the mitochondrial genome 12 (P = 1 × 10 −40 in an approximately uniform test). Estimation of divergence times suggests that the two high-altitude 'Himalaya' species R. bieti and R. strykeri diverged from the lowland R. avunculus species 0.80 million years ago and that the high-altitude northern species R. roxellana separated from the lowland R. brelichi species 1.07 million years ago ( Fig.…”
Section: Volume 48 | Number 8 | August 2016 Nature Genetics L E T T Ementioning
confidence: 49%
See 1 more Smart Citation
“…Regardless of the reference genomes and treebuilding methods used, the genome phylogeny strongly supported the interspecific relationships shown in a previous tree based on the analyses of several nuclear genes ( Fig. 1) and significantly rejected the relationships represented in a tree based on the mitochondrial genome 12 (P = 1 × 10 −40 in an approximately uniform test). Estimation of divergence times suggests that the two high-altitude 'Himalaya' species R. bieti and R. strykeri diverged from the lowland R. avunculus species 0.80 million years ago and that the high-altitude northern species R. roxellana separated from the lowland R. brelichi species 1.07 million years ago ( Fig.…”
Section: Volume 48 | Number 8 | August 2016 Nature Genetics L E T T Ementioning
confidence: 49%
“…We observed that the expression profiles of highly expressed genes from the digestive system (small intestine, large intestine, and stomach) and energyconsuming tissues (heart and skeletal muscle) were more similar in Phylogenetic relationships of the Rhinopithecus species inferred from a previous nuclear gene analysis 12 . The present whole-genome phylogeny supports the same relationships, regardless of the reference genomes and tree-building methods used.…”
Section: Volume 48 | Number 8 | August 2016 Nature Genetics L E T T Ementioning
confidence: 77%
“…Comparing orthologs between rhesus macaque and the snub-nosed monkeys, we reconstructed a maximum-likelihood phylogeny supporting the hypothesis of a separation between the northern species (R. roxellana and R. brelichi) and the 'Himalayan' species (R. bieti and R. strykeri) 25 with 100% bootstrap support values (Fig. 5a).…”
Section: Genomic Variation and Demographic Historymentioning
confidence: 62%
“…These times coincide with the uplift of the Tibetan plateau-Yuanmu movement (~1.6 million years ago)-which helped to create the higher mountains of the Himalayas 31 and might have resulted in the split of the northern and Himalayan species as well as the subsequent separation of R. roxellana and R. brelichi. Divergence within the Himalayan species appears to have begun about 0.3 million years ago, more recently than previously estimated 25 . The short branches of these lineages in the tree also imply that incomplete lineage sorting (ILS; cases where the gene tree was different from the species tree) and/or introgression have occurred within this clade.…”
Section: Genomic Variation and Demographic Historymentioning
confidence: 86%
See 1 more Smart Citation